Respuesta :

Answer:

x=5/3 your answer right answer

Answer:

110

Step-by-step explanation:

The expansion (a + b)³ is

(a + b)³ = a³ + b³ + 3ab(a + b)

Then

(x + [tex]\frac{1}{x}[/tex] )³ with a = x and b = [tex]\frac{1}{x}[/tex]

= x³ + [tex]\frac{1}{x^3}[/tex] + 3x . [tex]\frac{1}{x}[/tex] (x + [tex]\frac{1}{x}[/tex] )

Thus

x³ + [tex]\frac{1}{x^3}[/tex] = (x + [tex]\frac{1}{x}[/tex] )³ - 3(x + [tex]\frac{1}{x}[/tex] )

           = 5³ - 3(5)

           = 125 - 15

           = 110

ACCESS MORE